Formulation development and evaluation of controlled porosity osmotic pump delivery system for oral delivery of atenolol - Rathore, Garvendra S; Gupta, RN (Asian Journal of Pharmaceutics (AJP), 2014)
In the present study, we developed and evaluated the controlled porosity osmotic pump (CPOP) based drug deliverysystem of sparingly water soluble drug atenolol (ATL).We selected target release profile and optimized different variables to help us achieve this. Formulation variables, such as, the levels of solubility enhancer (0-15% w/w of drug), ratio of the drug to the osmogents, coat thickness of the semipermeable membrane (SPM) and level of pore former (0-20% w/w of polymer) were found to effect the drug release from the developed formulations. Cellulose acetate (CA 398-10) was used as the semipermeable membrane containing polyethylene glycol 400 as the Cplasticizer. ATL release was directly proportional to the level of the solubility enhancer, osmotic pressure generated by osmotic agent and level of pore former; however, was inversely proportional to the coat thickness of SPM. Drug release from developed formulations was independent of the pH and agitation intensities of release media. Burst strength of the exhausted shells decreased with increase in the level of pore former. The optimized formulations were subjected to stability studies as per International Conference on Harmonisation (ICH) guidelines, and formulations were found to be stable after 3 months study. Steady-state plasma levels of drug were predicted by the method of superposition.